Cooperative Fisheries Outperform Non-cooperative Ones in the Baltic Sea Under Different Climate Scenarios - Tunca, Sezgin; Lindegren, Martin; Ravn-Jonsen, Lars; Lindroos, Marko (Frontiers in Marine Science, 2019)
Game theory has been an effective tool to generate solutions for decision making in fisheries involving multiple countries and fleets. Here, we use a coupled bio-economic model based on a Baltic Sea dynamic multispecies food web model called BALMAR and, we compare non-cooperative (NC) and cooperative game (Grand Coalition: GC) solutions. Applications of game theory based on a food web model under climate change have not been studied before and the present study aims to fill this gap in the literature. The study focuses on the effects of climate variability on the biological, harvest and economic output of the game models by examining two different climate scenarios, a first scenario characterized by low temperature and high salinity and a second scenario by high temperature and low salinity. Our results showed that in the first scenario sprat spawning stock biomass (SSB) and harvest dropped dramatically both in the NC and the GC cases whereas, herring and cod SSBs and harvests were higher compared to a base scenario keeping temperature and salinity at mean historical levels. In the second scenario, the sprat SSB and the harvest was higher for both GC and NC cases while the cod and the herring SSBs and harvests were lower. The total GC payoffs clearly outperformed the NC payoffs across all scenarios. Likewise, the first and second scenario GC payoffs for countries were higher except for Poland. The findings suggested the climate vulnerability of Baltic Sea multi-species fisheries and these results would support future decision-making processes of Baltic Sea fisheries.